PROBLEMS AND FEATURES OF FORMS AND TYPES OF ORGANIZATION OF INNOVATIVE ACTIVITY IN THE METROPOLIS - V. Tikhonov (Вестник университета)
The article provides an overview of the problems and peculiarities in the forms and types of innovative activity in large cities, especially in metropolitan areas. Increasingly, the vector is directed priority funding for the development of cities, which helps to improve the development of innovation in these areas.